ANALISIS PENGARUH TINGKAT KESEHATAN BANK TERHADAP RETURN ON ASSET - Andy Setiawan (JURNAL LENTERA AKUNTANSI, 2016)
ABSTRACT  This research is performed on order to analyze the influence of the banking health toward Return On Asset (ROA) using Risk Based Bank Rating (RBBR) method. This research using Non  Performing  Loan  (NPL), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Capital Adequacy Ratio (CAR),  BOPO  (Biaya  Operasional/Pendapatan Operasional), Good Corporate Governance (GCG) and Posisi  Devisa  Netto  (PDN) as independent variable and Return on Asset (ROA) as dependent variable. Sample for this research is all of BUKU 4 bank  in Indonesia in 2007-2014 period. Data analysis with multi liniear regression. The result of  this research shows that all of RBBR variable has significant influence on ROA simultaneously.  LDR, NIM, BOPO, dan PDN  has significant influence partially toward ROA. But NPL, CAR and GCG did not influence ROA. Prediction capability from these seven variable toward ROA is 93,7% where the balance 6,3% is affected to other factor which was not to be entered to research model. Key Words : Risk based bank rating, BUKU 4, Return on Asset